PENGARUH PENGUMUMAN PERUBAHAN PERINGKAT OBLIGASI PERUSAHAAN TERHADAP REAKSI PASAR SAHAM - Pasanda, Eliab Izmar Beta; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research studies about the influence of the announcement of the changes of the bond level to the reaction of stock market in Indonesia Stock Exchange. The purposes of this research are to find out: 1) whether there is any influence the announcement of the changes of the bond level to the reaction of stock market in Indonesia Stock Exchange, 2) whether there is any influence of the annoucement of the changes of the decline of the bond level to the reaction of stock market in Indonesia Stock Exchange, 3) whether there is any significant influence around the date of the annoucement of the changes of the bond level which is shown by the average cumulative abnormal earnings to the reaction of stock market in Indonesia Stock Exchange. The results of the research show that: 1) the announcement of the decline of the bond level does not have any significant influence to the reaction of stock market in Indonesia Stock Exchange, 2) the announcement of the decline of the bond level does not have any influence to the reaction of stock market in Indonesia Stock Exchange and 3) the significant reaction of stock market on the date of the announcement of the bond level does not occur.Keywords: Bond Level, Reaction of Stock Market.